Question
upstudy study bank question image url

2. Resuelva el siguiente sistema de ecuaciones por el método de sustitución \( \begin{array}{l}x+y-z=-14 \\ x-3 y+2 z=16 \\ 2 x-2 y-3 z=5\end{array} \)

Ask by Todd Knight. in Ecuador
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La solución del sistema de ecuaciones es: \[ x = -\frac{107}{16}, \quad y = -\frac{129}{16}, \quad z = -\frac{3}{4} \] O en forma decimal: \[ x \approx -6.6875, \quad y \approx -8.0625, \quad z = -0.75 \]

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y-z=-14\\x-3y+2z=16\\2x-2y-3z=5\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-14-y+z\\x-3y+2z=16\\2x-2y-3z=5\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}-14-y+z-3y+2z=16\\2\left(-14-y+z\right)-2y-3z=5\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-14-4y+3z=16\\-28-4y-z=5\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}-14-4y+3z=16\\z=-33-4y\end{array}\right.\) - step5: Substitute the value of \(z:\) \(-14-4y+3\left(-33-4y\right)=16\) - step6: Simplify: \(-113-16y=16\) - step7: Move the constant to the right side: \(-16y=16+113\) - step8: Add the numbers: \(-16y=129\) - step9: Change the signs: \(16y=-129\) - step10: Divide both sides: \(\frac{16y}{16}=\frac{-129}{16}\) - step11: Divide the numbers: \(y=-\frac{129}{16}\) - step12: Substitute the value of \(y:\) \(z=-33-4\left(-\frac{129}{16}\right)\) - step13: Calculate: \(z=-\frac{3}{4}\) - step14: Substitute the values of \(y,z:\) \(x=-14-\left(-\frac{129}{16}\right)-\frac{3}{4}\) - step15: Substitute back: \(x=-14+\frac{129}{16}-\frac{3}{4}\) - step16: Calculate: \(x=-\frac{107}{16}\) - step17: Calculate: \(\left\{ \begin{array}{l}x=-\frac{107}{16}\\y=-\frac{129}{16}\\z=-\frac{3}{4}\end{array}\right.\) - step18: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{107}{16}\\y=-\frac{129}{16}\\z=-\frac{3}{4}\end{array}\right.\) - step19: Rewrite: \(\left(x,y,z\right) = \left(-\frac{107}{16},-\frac{129}{16},-\frac{3}{4}\right)\) Para resolver el sistema de ecuaciones por el método de sustitución, seguimos estos pasos: 1. **Identificar las ecuaciones**: \[ \begin{array}{l} (1) \quad x + y - z = -14 \\ (2) \quad x - 3y + 2z = 16 \\ (3) \quad 2x - 2y - 3z = 5 \end{array} \] 2. **Despejar una variable**: Vamos a despejar \( z \) de la primera ecuación (1): \[ z = x + y + 14 \] 3. **Sustituir \( z \) en las otras ecuaciones**: Sustituyendo \( z \) en la segunda ecuación (2): \[ x - 3y + 2(x + y + 14) = 16 \] Simplificando: \[ x - 3y + 2x + 2y + 28 = 16 \\ 3x - y + 28 = 16 \\ 3x - y = -12 \quad (4) \] Ahora sustituimos \( z \) en la tercera ecuación (3): \[ 2x - 2y - 3(x + y + 14) = 5 \] Simplificando: \[ 2x - 2y - 3x - 3y - 42 = 5 \\ -x - 5y - 42 = 5 \\ -x - 5y = 47 \quad (5) \] 4. **Resolver el nuevo sistema de ecuaciones**: Ahora tenemos el siguiente sistema: \[ \begin{array}{l} (4) \quad 3x - y = -12 \\ (5) \quad -x - 5y = 47 \end{array} \] Despejamos \( y \) de la ecuación (4): \[ y = 3x + 12 \] Sustituyendo \( y \) en la ecuación (5): \[ -x - 5(3x + 12) = 47 \\ -x - 15x - 60 = 47 \\ -16x - 60 = 47 \\ -16x = 107 \\ x = -\frac{107}{16} \] 5. **Encontrar \( y \) y \( z \)**: Sustituyendo \( x \) en la ecuación para \( y \): \[ y = 3\left(-\frac{107}{16}\right) + 12 \\ y = -\frac{321}{16} + \frac{192}{16} \\ y = -\frac{129}{16} \] Finalmente, sustituimos \( x \) y \( y \) en la ecuación para \( z \): \[ z = -\frac{107}{16} + -\frac{129}{16} + 14 \\ z = -\frac{236}{16} + \frac{224}{16} \\ z = -\frac{12}{16} = -\frac{3}{4} \] 6. **Resultado final**: La solución del sistema de ecuaciones es: \[ (x, y, z) = \left(-\frac{107}{16}, -\frac{129}{16}, -\frac{3}{4}\right) \] O en forma decimal: \[ (x, y, z) = (-6.6875, -8.0625, -0.75) \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Primero, despejemos \(z\) de la primera ecuación. De \(x + y - z = -14\), podemos escribir \(z = x + y + 14\). Ahora sustituimos \(z\) en las otras dos ecuaciones: 1. \(x - 3y + 2(x + y + 14) = 16\) 2. \(2x - 2y - 3(x + y + 14) = 5\) Resolviendo la primera ecuación: \(x - 3y + 2x + 2y + 28 = 16\) \(3x - y + 28 = 16\) \(3x - y = -12\) Ahora la segunda ecuación: \(2x - 2y - 3x - 3y - 42 = 5\) \(-x - 5y - 42 = 5\) \(-x - 5y = 47\) \(x + 5y = -47\) Ahora tenemos el nuevo sistema: \[ \begin{array}{l} 3x - y = -12 \\ x + 5y = -47 \end{array} \] Despejamos \(y\) de la primera ecuación: \(y = 3x + 12\) Sustituimos \(y\) en la segunda ecuación: \(x + 5(3x + 12) = -47\) \(x + 15x + 60 = -47\) \(16x + 60 = -47\) \(16x = -107\) \(x = -\frac{107}{16}\) Ahora sustituimos \(x\) en \(y = 3x + 12\): \(y = 3\left(-\frac{107}{16}\right) + 12\) \(y = -\frac{321}{16} + \frac{192}{16}\) \(y = -\frac{129}{16}\) Finalmente, encontramos \(z\): \(z = -\frac{107}{16} - \frac{129}{16} + 14\) \(z = -\frac{236}{16} + \frac{224}{16}\) \(z = -\frac{12}{16} = -\frac{3}{4}\) Entonces, la solución del sistema es: \[ x = -\frac{107}{16}, \quad y = -\frac{129}{16}, \quad z = -\frac{3}{4} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy